The impact of silicone hydrogel contact lenses on the measurement of intraocular pressure using non-contact tonometry - Pešić, Snežana; Jovanović, Svetlana; Mitrašević, Miloš; Vuletić, Biljana; Jovanović, Milena; Jovanović, Zorica (Vojnosanitetski pregled, 2017)
Background/Aim. Measurement of intraocular pressure (IOP) over therapeutic silicone hydrogel soft contact lenses by a non-contact method of tonometry could be applied in opthalmologic practice but the results obtained are still controversial. The aim of this study was to evaluate the effect of spherically designed silicone hydrogel soft contact lenses and their power on values of IOP measured by using a non-contact tonometry method. Methods. We measured IOP with and without spherical silicone hydrogel soft contact lenses on 143 eyes of 80 subjects who did not have any ocular or systemic diseases. Results. The Wilcoxon statistical analysis test for ranking average values ​​of IOP measured on 143 eyes over a spherical silicone hydrogel soft contact lenses showed significantly higher values ​​compared to those measured  with no contact lenses (15.81 ± 3.46 mm Hg vs 14.54 ± 3.19 mm Hg; respectively; Z = -5.224, p = 0.001). Refractive power analysis of the contact lenses of -9.00D to +6.00 D showed a significant difference of IOP in the range from 0.00D to -6.00D. Conclusion. Non-contact tonometry is not an accurate method of IOP measuring over spherical silicone hydrogel soft contact lenses which belong to therapeutic contact lenses.
Keywords: intraocular pressure; tonometry; ocular; diagnostic errors; contact lenses; hydrophylic